Perilaku Komunikasi Remaja Dengan Orang Tua Dalam Penggunaan Produk Virtual Dalam Game Online Mobile Legends: Bang Bang - Evan Setia Ferryan; Atwar Bajari; Teddy Kurnia Wirakusumah (Institut Nalanda, 2024)
This study aims to determine the motives of teenagers in purchasing and using virtual products in the Mobile Legends: Bang Bang online game, teenagers' communication experience in using virtual products in Mobile Legends: Bang Bang, and teenagers' communication behavior with parents in using virtual products in Mobile Legends: Bang Bang. This research uses a qualitative phenomenological approach with Phenomenology Theory. Data collection techniques in this research is using in-depth interviews and observation. Informant selection in this research is using purposive sampling technique. Then, data analysis in this research is using the Miles & Huberman interactive analysis technique. The results showed that there are two motives for teenagers to buy and use virtual products in the Mobile Legends: Bang Bang, namely because-motive which includes the appearance and aesthetics of virtual products, playing and liking heroes from virtual products, not wanting to be inferior to the surrounding environment, and in-order-to motive which includes to improve playing skills, to show off their virtual products, and to gain a sense of prestige and recognition from the surrounding environment. Communication experiences experienced by teenagers in using virtual products are divided into three, namely with parents, the environment, and themselves, all three of which tend to be positive communication experiences. Then, there are meanings about virtual products and relationships between teenagers and parents formed from communication behavior between them regarding the use of virtual products, teenagers interpret virtual products as pride, self-reward, investment, personalization, hobbies, lifestyle, and teenagers interpret their relationship with their parents as encouragement, good communication, parental affection, and reciprocal relationships.